Rancang Bangun Mesin Blender Buah - Nur Hayati (Universitas Sarjanawiyata Tamansiswa, 2019)
Technology makes everything done easier. This is what drives the development of technology that has producedmany tools as tools to facilitate human activities and even replace the role of humans in a particular function.However, this development has not been seen in industrial sectors that utilize conventional energy, for exampleinfruit blender machines. This study describes the making of a larger capacity fruit blender machine that cansimplify work and not take a long time. Making a fruit blender machine begins with making design drawings,making components and assembling all components intoa fruit blender machine. With this machine, it isexpected that the community can be easier. In doing work without taking a long time to get a lot of results,especially for people who have businesses in the field of fruit production.